EFEKTIVITAS KEPENGAWASAN KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME TENAGA PENDIDIK DI MADRASAH ALIYAH NEGERI BEUREUNUEN - Sabirin, Cut Zahri Harun, Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
ABSTRACT: Supervisory principals improve the professionalism of teachers can improve teacher competence. The aim of this study was to obtain data about the program, the implementation of the oversight conducted by the principal, and obstacles in carrying out supervisory teaching to improve teacher performance. This study used a qualitative approach, descriptive methods, data collection techniques of observation, interviews and documentation study, subjects qualitative research Principals and teachers MAN Beureuneuen Pidie and data processing through qualitative analysis, Penelitian gives conclusions: (1) The head of the school has put together a program supervisory specifically based on the results of the analysis of the needs and problems experienced teachers; (2) the implementation of supervisory teaching effectively implemented in accordance with a program that had been developed together with the techniques of individual and group techniques; (3) supervisory evaluation of principals in improving the professionalism of teachers in Madrasah Aliyah Negeri Beureunuen done with coaching, individually or in groups regularly and continuously, so as to produce professional teachers in accordance with their respective field; and (4) the barriers experienced by principals in implementing the internal oversight is the attitude of teachers in accepting guidance, and external constraints are the number of inspectors is limited and they are forced to build different teachers their field of study. Based on these results suggested that the government commissioned a study or field supervisor personnel provide specialized training to them.Keywords: supervisory, teaching, and teacher performance ABSTRAK: Kepengawasan kepala sekolah meningkatkan profesionalisme tenaga pendidik dapat meningkatkan kompetensi guru. Penelitian ini bertujuan untuk mendapatkan data tentang program, pelaksanaan kepengawasan yang dilaksanakan oleh kepala sekolah, dan hambatan-hambatan dalam melaksanakan kepengawasan pengajaran untuk meningkatkan kinerja guru. Penelitian ini menggunakan pendekatan kualitatif, metode deskriptif, teknik pengumpulan data observasi, wawancara dan studi dokumentasi, subjek penelitian kualitatif Kepala Sekolah dan guru MAN Beureuneuen Kabupaten Pidie, dan pengolahan data melalui analisis kualitatif, Penelitian ini memberikan kesimpulan: (1) kepala Sekolah telah menyusun program kepengawasan secara khusus berdasarkan hasil analisis kebutuhan dan masalah yang dialami guru; (2) pelaksanaan kepengawasan pengajaran dilaksanakan secara efektif sesuai dengan program yang telah disusun bersama dengan teknik perorangan dan teknik kelompok; (3) evaluasi kepengawasan kepala sekolah dalam meningkatkan profesionalisme tenaga pendidik di Madrasah Aliyah Negeri Beureunuen dilakukan dengan pembinaan secara individual maupun berkelompok secara rutin dan berkesinambungan, sehingga menghasilkan guru-guru yang profesional sesuai dengan bidangnya masing-masing; dan (4) hambatan-hambatan yang dialami kepala sekolah dalam melaksanakan kepengawasan yang bersifat internal adalah sikap guru dalam menerima pembinaan, dan hambatan eksternal adalah jumlah pengawas terbatas dan mereka terpaksa membina guru yang berbeda bidang studinya. Berdasarkan hasil ini disarankan agar pemerintah menugaskan tenaga supervisor bidang studi atau memberi pelatihan khusus kepada mereka.Kata kunci: kepengawasan, pengajaran, dan kinerja guru